Identifying Factors Alleviating Poverty: Experience from Malaysian Zakat Institutions - Mohamed Saladin Abdul Rasool; Sharifah Adlina Tuan Sayed Amran (Center of Strategic Studies (PUSKAS) BAZNAS, 2017)
A major challenge for zakat institutions is to identify ways to alleviate poverty. Thus, it is essential to determine factors that influence the incidence of poverty. Determinants of poverty can be used by zakat institutions as a guide by zakat authorities as to draw guidelines and programs to alleviate the poor. The objective of the present paper is to identify the determinants of poverty from the perspective of poor zakat recepients in Selangor, the most populated Muslim state in Malaysia. Using the Had Kifayah method, which is based on maqasid al-shariah principles, the study would outline factors that can be used as a guideline to fight poverty. The present study employed a dataset derived from a survey consisting of 258 head of household heads of low-income group in the state of Selangor, the most populated state in Malaysia. The multiple linear regression (MLR) analysis revealed three factors that influence poverty in this study, namely, unemployment of household heads, non-working household adults and unability to obtain permanent jobs. Keywords: Poverty, measurements, zakat organizations